Esterified Illipe Butter-Based Fatty Amine as a Bio-Based Multifunctional Additive for NR/BR Blends Reinforced with a Silica/Silane System in Green Tire Tread Development - Fathurrohman, Mohamad Irfan; Puspitasari, Santi; Kinasih, Norma Arisanti; Arti, Dewi Kusuma (Green Engineering Society, 2025)
The sustainable rubber industry, particularly in the tire sector, is supported by the use of biomaterials such as multifunctional additives. Fatty amine, derived from the esterification of illipe butter, is considered a promising bio-based multifunctional additive for the development of green tires. This research aimed to investigate the effect of varying dosage of fatty amine on the properties of green tire treads based on NR/BR blends reinforced with a silica/silane system. DPG and unmodified illipe butter were used as comparative references. The